Theoretical aspects of quality assurance of education at local level - POPA, Violeta (Acta et Commentationes, Sciences of Education, 2022)
In the article, we make a foray into the key concepts: quality, quality in education, quality assurance, quality management, quality management in education. The structure, functions, processes, components and implementation procedures of the Quality Assurance System at local level are presented, reporting on the responsibility of OLSDÎ on quality assurance, as well as on the current situation in the Republic of Moldova on quality management of education at local level.